Meckel's Diverticulitis. A rare cause of small bowel obstruction. Issue 9 (30th September 2020) - Skarpas, Andreas; Siaperas, Petros; Zoikas, Athanasios; Griva, Emmanouela; Kyriazis, Ioannis; Velimezis, Georgios; Karanikas, Ioannis
Abstract: Meckel's Diverticulum is a sac-like protrusion of the intestinal wall. It is located at 40–60 cm from the caecum. In the majority of cases, Meckel's Diverticulum is clinically silent, while complications are found in 4% of the population. Complicated diverticulitis is associated with the formation of abscess, fistula, bowel obstruction or frank perforation. We present a case of a 63-year-old woman with a distended abdomen, pain in the lower right abdominal quadrant, fever 37°C and where emergency exploratory laparotomy revealed that obstruction was caused by a bowel loop trapped by a mesenterium-diverticular band.